2018
DOI: 10.1371/journal.pone.0206987
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B viruses circulated during last 5 years in Mongolia

Abstract: Influenza B virus-caused illness has recently been considered as an urgent public health problem due to substantial morbidity, mortality and life-threatening medical complications. In this study, we have reported the main characteristics of influenza B virus in Mongolia, including prevalence, lineages, suitability with vaccine strains and drug susceptibility against the virus. 15768 specimens were tested by qPCR for detecting influenza viruses. From positive specimens for influenza B virus, the clinical isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…During the study period, different patterns of Victoria and Yamagata-lineage B viruses were observed. Regarding the distribution of the different lineages in relation to the age groups of the population studied, our study showed that both the Victoria and Yamagata viruses were more likely to infect patients aged between five and 14 years, which had also been observed in previous studies [32,33,[40][41][42]. Moreover, it can be observed that Victoria lineage viruses tend to be distributed according to age with a peak in children under 10 years.…”
Section: Discussionsupporting
confidence: 87%
“…During the study period, different patterns of Victoria and Yamagata-lineage B viruses were observed. Regarding the distribution of the different lineages in relation to the age groups of the population studied, our study showed that both the Victoria and Yamagata viruses were more likely to infect patients aged between five and 14 years, which had also been observed in previous studies [32,33,[40][41][42]. Moreover, it can be observed that Victoria lineage viruses tend to be distributed according to age with a peak in children under 10 years.…”
Section: Discussionsupporting
confidence: 87%
“…While the exact mechanism for this is not clear, molecular studies suggest that large populations in the tropics can serve as reservoirs of influenza infection throughout the year, with reseeding of drifted viruses possibly leading to outbreaks 29 . However, in the later years, during 2012 to 2013, seasonal Influenza B and H3N2 strains were frequently seen mirroring the global picture 30,31 . In recent years (2014‐2016), there has been a resurgence of A/H1N1 which is reported globally as well 32‐34 .…”
Section: Discussionmentioning
confidence: 99%
“…29 However, in the later years, during 2012 to 2013, seasonal Influenza B and H3N2 strains were frequently seen mirroring the global picture. 30,31 In recent years (2014-2016), there has been a resurgence of A/H1N1 which is reported globally as well. This has been attributed to genetic reassortment of the virus, rapid change in environmental conditions and decrease in host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 100% of seasonal H3N2 and 99.8% of 2009 pandemic influenza samples was found resistant to adamantanes, M2 inhibitor [ 28 ]. Similarly, due to mutation at particular amino acid, NA inhibitors-resistant human isolates gradually emerged, like H1N1 (NA-I222V/M/L/R/T, H274Y and S334N) [ 29 ], H3N2 (NA-E119V, E11V) [ 30 ], H7N9 (NA-R292K) [ 31 ] and IBV (NA-G104R) [ 32 ]. Given that IBV also has the antigenic drift and can develop drug-resistance, identifying and developing new antiviral drugs is imperative.…”
Section: Discussionmentioning
confidence: 99%